Development of Biodegradable Films Based on Chitosan/Glycerol Blends Suitable for Biomedical Applications - Debandi, María Valeria (2016)
In the present work, chitosan/glycerol blends were used to prepare biodegradable films with potential applicationin dermal treatment. While the presence of glycerol gives the hydrating effect, the chitosan characteristics contribute to dermal regeneration. Swelling degree measurements, water vapor permeability determinations, mechanical tests, scanning electronic microscopy and Fourier transform infrared spectroscopy analysis; biodegradability studies, thermogravimetric and differential scanning calorimetry analysis were used to analyze the influence of the incorporation of significant amounts of glycerol in film properties. The obtained results suggested that the glycerol addition provide the films with the required properties for the intended application related to dermal treatment. Increasing the glycerol concentration, a cluster effect produced by the glycerol molecules surrounding the macromolecular chains led to a decrease in the swelling degree and an increase in the WVP along with improvements in mechanical properties.